Strategies to Improve Oral Communication Ability through Early Children's Show and Tell Method - Rezki Perwita Arum; Khamim Zarkasih Putro; Agus Jatmiko; Na'imah (JOYCED: Journal of Early Childhood Education, 2022)
Oral communication has an important aspect in early childhood. There are various activities that can be carried out in developing oral communication for early childhood, but sometimes children feel bored and bored in class because teachers teach only focused on magazines which causes the development of oral communication has not developed. The purpose of this study was to develop children's oral communication through the show and tell method at Karana Jaya Kindergarten, Lampung. This research is a descriptive research with a qualitative approach. The research subjects were 19 children aged 5-6 years. Data collection techniques using observation, interviews and documentation. The results showed that in addition to the activities contained in the magazine to develop children's creativity, This show and tell activity is one of the right activities to do in developing children's oral communication. The conclusion of this research is to develop and improve oral communication skills through the show and tell method.